Calculation Of Aircraft Emission Reduction During The Taxi-Out Phase With The Implementation Of Single Engine Operation At Kertajati Airport - Persada, Pintanugra (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2025)
The aviation sector is estimated to contribute about 2% of total CO2 emissions due to human activities. Increased aviation activity at Kertajati Airport has the potential to increase aircraft gas emissions, making the evaluation of emission reduction strategies very important. The main focus of this research is to analyze the effectiveness of single-engine taxi operations during the taxi-out phase in reducing emissions. Using a hybrid approach that combines Advanced Approach and Sophisticated Approach, this quantitative study examines emissions of Hydrocarbons (HC), Carbon Monoxide (CO), and Nitrogen Oxides (NOx). The analysis compares normal operations with single-engine taxi operations during the taxi-out phase. Research results show that in normal operations, total emissions during the taxi-out phase are HC: 22,328.55 grams, CO: 961,184.10 grams, and NOx: 193,381.07 grams. The implementation of single-engine taxi strategy significantly reduces emissions to HC: 6,841.11 grams, CO: 326,101.67 grams, and NOx: 63,002.80 grams. Key findings indicate substantial emission reductions: 69% for HC, 66% for CO, and 67% for NOx. These results demonstrate the effectiveness of single-engine taxi operations in mitigating the environmental impact of aircraft operations at Kertajati Airport. This study provides valuable insights for airport managers and aviation industry stakeholders in developing more environmentally friendly operational practices. The implementation of this strategy has the potential to significantly contribute to efforts in reducing the carbon footprint of the aviation sector, aligning with global commitments to mitigate climate change.